Investigation into the relationship among Cd bioaccumulation, nutrient composition, ultrastructural changes and antioxidative metabolism in lettuce genotypes under Cd stress - Lavres, José; Silveira Rabêlo, Flávio Henrique; Capaldi, Flávia Regina; dos Reis, André Rodrigues [UNESP]; Rosssi, Monica Lanzoni; Franco, Mônica Regina; Azevedo, Ricardo Antunes; Abreu-Junior, Cassio Hamilton; de Lima Nogueira, Neusa (Elsevier, 2019)
Lettuce (Lactuca sativa L.) is known to have high cadmium (Cd) concentrations in its shoots, which makes it necessary to protect against Cd toxicity. Understanding Cd-induced physiological responses in lettuce plants can contribute to the definition of useful strategies to decrease Cd uptake. This study aimed to gain new insights into Cd-induced stress by measuring Cd bioaccumulation, nutrient composition, anatomical and ultrastructural changes, and antioxidative metabolism in three lettuce genotypes characterized as having different degrees of Cd tolerance (Vanda = low, Lidia = medium and Stela = high). Plants were grown hydroponically with Cd concentrations of 0.0 and 0.1 or 0.5 μmol L −1 , for 30 days. Cadmium uptake in the lettuce genotypes assayed is controlled by the root/shoot ratio, higher root/shoot ratios allowing greater Cd uptake. The Fe and Ni content increased in shoots of the genotype Lidia, which could be associated with a decrease in oxidative stress in chloroplasts due to superoxide dismutase (SOD) isozyme activity. Cadmium-induced oxidative stress is associated with de-structuring of the phloem and xylem in roots, and starch grain and plastoglobule accumulation in chloroplasts. Lettuce genotypes that presented higher SOD and ascorbate peroxidase (APX) activity presented better preserved anatomical structures. These results suggest that genotypes with less efficient antioxidant defence in the roots tend to take up more Cd, increasing root-to-shoot Cd translocation.
Keywords: Ionomics; Lactuca sativa; Lipid peroxidation; Oxidative stress; Scanning electron microscopy